Performance and Emissions Comparison between Biomethane and Natural Gas Fuel in Passenger Vehicles: results of the second testing campaign - Cignini Fabio (EDP Sciences, 2021)
The present paper illustrates the results of the second set of measurements carried out in the BiomethER project (EU-LIFE). BiomethER aimed to design and build two innovative bio-methane production plants, located in the Emilia Romagna region (Italy), so it aims to demonstrate that bio‑methane could replace traditional methane in several applications. One of these applications is road transport where bio-methane can fuel a compressed natural gas (CNG) vehicle. So, three passenger cars have been tested with two gases: conventional natural gas and bio-methane coming from a BiomethER plant. For each vehicle have been measured the emissions and performances on the chassis dynamometer, while an inspection of combustion chambers of the engines was carried out to evaluate their wear condition. This campaign confirms results achieved in the first one, there are no appreciable deviations for fuel consumption and CO2 emissions between the two fuels, acceleration and maximum power were almost the same for the three vehicles tested. Indeed, the vehicle fuelled by methane has significant carbon deposits on the piston crown while the bio-methane fuelled do not have the same.